Niif y sus beneficios y afectaciones en la economía de una empresa ubicada en la ciudad de Duitama - Gamboa Caicedo, María Paz (Universidad Antonio Nariño, 2024)
The purpose of the adoption of International Financial Reporting Standards in Colombia is to allow companies to compete internationally following globally accepted economic and financial standards. This translates into improved competitiveness in international markets, by guaranteeing the reliability and understanding of financial information. This encourages making wise decisions that ultimately benefit the organization.